47/#736 CRS-HIPEC in upfront versus interval setting for advanced epithelial ovarian cancer – cut when fit not when fatigued. (4th December 2022) - Somashekhar, Sp; Kumar, Rohit; Yethadka, Ramya; Rauthan, Amit; Fernandes, Aaron; Karthik, HK; Rajagopal, Ashwin
Abstract : Objectives: Cytoreductive surgery with HIPEC has shown promising results in interval setting in advanced epithelial ovarian cancer. Its role in upfront setting has not yet been established. Methods: All eligible patients underwent CRS HIPEC as per institution protocol. Relevant data was entered prospectively in institutional HIPEC registry and analysed retrospectively for study period from February 2014 – February 2019. Results: Out of 190 patients, 80 underwent CRS HIPEC in upfront setting and 110 in interval setting. Median age was 54±7.45 years, upfront group had higher PCI (14.1±8.75 VS. 9.6±5.2. 2), and required longer duration of surgery (10.6±1.73 vs. 8.4±1.71 hrs) had more blood loss (1025±668.76 vs.680±302.23 ml). Upfront group required more diaphragmatic resections, bowel resections and multivisceral resections. The overall G3-G4 morbidity was comparable (25.4%vs. 27.3%), upfront group had more surgical morbidity (20%vs.9.1%) whereas interval group had more medical morbidity i.e. electrolyte imbalance and haematological. After a median follow up of 43 months, median DFS was 33 months in upfront vs. 30 months in interval group, p=0.75, median OS was 46 months interval group and was not yet achieved in upfront group.(p=0.13). 4 year OS was 85%vs 60%. Performance status (P =0.025 C.I 1.190–12.80) was the only factor predicting morbidity on multivariate analysis. Conclusions: In patients of advanced EOC upfront CRS HIPEC showed promising outcomes and better survival with similar morbidity and mortality. Upfront group had more surgical morbidity whereas interval group had more medical morbidity. Multi-institutional randomised studies are needed to define patient selection and study morbidity patterns.